(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The appeal to the work of Akimzhan Zheenbai in this work is due to the fact that in modern Kyrgyz musicology there are almost no works devoted to the activities of composers of the 70s – 80s, with the exception of several student works. Meanwhile, the work of many talented composers who came to art in the late 60s in the early 70s – Satylgan Osmonov, Asan Murzabaev, Esengul Dzhumabaev, Zhyldyz Maldybaeva, Vladimir Gusev, not to mention composers of a younger generation, is of great interest for research. Each of these musicians has an individual creative style, great artistic potential, a variety of interests, a vast, diverse heritage. Of undeniable interest are the musical compositions of A. Zheenbai, who has long gained their listeners and are very popular in the republic ( especially his choral, song and chamber-instrumental compositions). A. Zheenbai`s work is devoted to a number of articles and reviews in republican and international newspapers and magazines, a short biographical essay in the handbook «Composers of Kyrgyzstan». Some observations about his music are contained in articles and monographs. This gap was tried by the author of the present work. When writing it, some observations contained in published materials, the author`s personal observations, factual data drawn from numerous conversations with the composer, as well as the results of analysis of his works were used. The purpose of the work is the author`s desire to explore in a more detailed form the composer`s life path, the evolution of his style and creativity with an analysis of the most significant and indicative works for the musician. Undoubtedly, the work of composer Akimzhan Zheenbai deserves further study.